Impact of Environmental Policy Factors on Tourism Industry: A Study from Indonesia Over Last Three Decades - Andriansyah, Andriansyah; Taufiqurokhman, Taufiqurokhman; Wekke, Ismail Suardi (International Journal of Energy Economics and Policy, 2019)
The purpose of the present study analysis is to empirically examine the impact of various environmental factors on the Tourism industry in Indonesia. To achieve this objective, data is collected from World Development Indicators (WDI) during the time of 1996-2016 under the title of environmental factors as defined by the experts of the world bank. A time of 22 years has been finalized for the predictors of tourism industry like forest area, population growth, energy use, agriculture, forestry and fishing along with CO2 emissions. Both descriptive and regression analysis techniques have been applied while adding the lagged predictors of both tourism industry and environmental factors. Eight regression models have been developed and results are generated through statistical tools like STATA-14. Findings of the study indicate that forest area and population growth are the significant determinants of the tourism industry. Among the lagged predictors, international tourism (lagged), Nitrous oxide emissions, and lagged values of forest areas are significantly affecting international tourism receipt in the region of Indonesia. For the 2nd proxy; tourism expenditures, the key determinants under model 5-8 are, international tourism (lagged), Nitrous oxide emissions (lagged), CO2 emission (lagged) and population growth. As per the practical implications, this study is very much useful for both the industry experts and policymakers at macro-level. Considering the set of factors as explained in the present study will provide new insight regarding sustainable development through environmental factors of the tourism industry. However, the key limitations are the lack of advance time series investigation, ignoring the impact of macroeconomic indicators and cross region analysis. Keywords: World Development Indicators, Environmental Factors, Tourism Industry, Indonesia JEL Classifications: Q56, R11 DOI: https://doi.org/10.32479/ijeep.7754